2019
DOI: 10.1063/1.5057424
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the composition-dependence of the energy bandgap of GaAsNBi alloys

Abstract: We have examined the alloy composition dependence of the energy bandgap and electronic states in GaAsNBi alloys. Using direct measurements of N and Bi mole fractions, via ion beam analysis, in conjunction with direct measurements of the out-of-plane misfit via x-ray rocking curves, we determine the “magic ratio” for lattice-matching of GaAsNBi alloys with GaAs substrates. In addition, using a combination of photoreflectance and photoluminescence spectroscopy, we map the composition- and misfit-dependence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Consequently, the quaternary GaNAsBi alloy on GaAs can cover a wide spectral range of the nearinfrared with flexible control of the band offsets. 1,[4][5][6] In addition, this alloy can be lattice-matched to GaAs by controlling the composition of N and Bi. 1,6) Based on these advantages, optoelectronic devices, such as light-emitting diodes 7) and solar cells, 8) have been prototyped.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the quaternary GaNAsBi alloy on GaAs can cover a wide spectral range of the nearinfrared with flexible control of the band offsets. 1,[4][5][6] In addition, this alloy can be lattice-matched to GaAs by controlling the composition of N and Bi. 1,6) Based on these advantages, optoelectronic devices, such as light-emitting diodes 7) and solar cells, 8) have been prototyped.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the molar ratio of nitrogen to bismuth for GaAsNBi matching to GaAs should be equal to 0.59, 21) although a recent paper suggests a revised value of 0.61. 22) The temperature dependence of the band-gap energy of semiconductors represents a basic material-specific property which is of substantial practical and also theoretical interest. It is well known that the band-gap of semiconductors decreases monotonically with increasing temperature due to dilation of the lattice constant and the temperature-dependent electron-phonon interaction.…”
mentioning
confidence: 99%
“…Figure 1 shows the calculated band structure close to the Γ point of GaAs and a GaAs 0.926 N 0.018 Bi 0.056 alloy to illustrate the Bi-and N-induced band-gap reduction based on the previous report. 22) The calculation was carried out under the assumption that the valence band edge moves according to the valence band anticrossing (VBAC) model and the conduction band minimum shifts according to the CBAC model. 5,14) Figure 1 also depicts the localized Bi 6p-like states at 0.4 eV below the GaAs VBM (valence band maximum), spin-orbit split energy for the bismuth = -E 1.9 eV Bi SO below VBM of GaAs, and the resonant energy of nitrogen level E N = ∼1.65 eV above the top of the GaAs VBM.…”
mentioning
confidence: 99%
See 2 more Smart Citations